The complete chloroplast genome sequence of the Canna edulis Ker Gawl. (Cannaceae) - Qianglong Zhu; Lijuan Cai; Huiying Li; Yu Zhang; Wenzhen Su; Qinghong Zhou (Mitochondrial DNA. Part B. Resources, 2020)
Canna edulis Ker Gawl. is an essential traditional tuber crop used for fresh consumption and to isolate starch in some tropical and semitropical regions. The complete chloroplast genome sequence of C. edulis has been determined in this study. The total genome size is 164,650 bp in length and contains a pair of inverted repeats (IRs) of 27,278 bp, which were separated by large single-copy (LSC) and small single-copy (SSC) of 91,421 bp and 18,673 bp, respectively. A total of 131 genes were predicted including 86 protein-coding genes, 8 rRNA genes and 37 tRNA genes. Further, maximum-likelihood phylogenetic analysis revealed that C. edulis belongs to Cannaceae in Zingiberales. The chloroplast genome of C. edulis is first complete genome sequence in Cannaceae and would play a significant role in the development of molecular markers in plant phylogenetic and population genetic studies.